2022
DOI: 10.1002/lt.26562
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients with Liver Imaging Reporting and Data System 3 or Liver Imaging Reporting and Data System 4 observations in patients with cirrhosis: A systematic review

Abstract: Patients with indeterminate liver nodules, classified as LR-3 and LR-4 observations per the Liver Imaging Reporting and Data System, are at risk of developing hepatocellular carcinoma (HCC), but risk estimates remain imprecise. We conducted a systematic review of Ovid MEDLINE, EMBASE, and Cochrane databases from inception to December 2021 to identify cohort studies examining HCC incidence among patients with LR-3 or LR-4 observations on computed tomography (CT) or magnetic resonance imaging (MRI).Predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Harms in the FP group were also likely mitigated by the quick resolution of the findings, with many patients simply undergoing a single CT or MRI, without need for a biopsy. Patients with indeterminate liver lesions (eg, LI-RADS 3 or 4 lesions) have an intermediate risk of developing HCC, [33] and some undergo prolonged, repeated imaging, which may result in increased psychological distress compared to others. Therefore, although psychological harms in our study were mild compared to other cancers, there may still be subgroups who experience greater psychological distress and for whom counseling or other interventions may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harms in the FP group were also likely mitigated by the quick resolution of the findings, with many patients simply undergoing a single CT or MRI, without need for a biopsy. Patients with indeterminate liver lesions (eg, LI-RADS 3 or 4 lesions) have an intermediate risk of developing HCC, [33] and some undergo prolonged, repeated imaging, which may result in increased psychological distress compared to others. Therefore, although psychological harms in our study were mild compared to other cancers, there may still be subgroups who experience greater psychological distress and for whom counseling or other interventions may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…TPs were defined as the detection of HCC on follow-up testing within 1 year of the positive surveillance test; FP was defined as no HCC within 1 year of the positive test; and TN remained HCC free for at least 1 year after the negative screening result. A 1-year cutoff was selected to allow sufficient time for cancer adjudication, given longer periods can be required for patients with indeterminate nodules on diagnostic CT or MR imaging 22,32–34 . Although false-negative results may result in psychosocial harms, we did not anticipate having sufficient patients for this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…83 Patients with indeterminate liver nodules (LI-RADS 3 or LI-RADS 4) have an intermediate risk of HCC, between 35-65%, so typically warrant close follow-up imaging, with biopsies used in cases that would change immediate clinical management. [84][85][86] Patients without cirrhosis or high-risk HBV should undergo biopsy for histologic confirmation, as imaging features have insufficient accuracy. 49 Although a diagnosis of HCC can be made radiographically in most cases, approximately 10% of HCCs will have atypical imaging features (e.g., arterial phase hyperenhancement alone or delayed washout alone).…”
Section: Recall and Diagnosismentioning
confidence: 99%
“…[2] In patients with LR-4 observations, multidisciplinary discussions regarding treatment implications can help decide optimal follow-up, including repeat imaging within 3 months or immediate biopsy. [2] A routine biopsy of every LR-4 observation is not recommended given the risk of bleeding, tumor seeding, and false negative results; however, a biopsy may be warranted depending on factors including the size of the T A B L E 1 Factors associated with the development of HCC in patients with ILNs [7] Patient observation, transplant eligibility, and tumor marker levels. For example, a biopsy could be important for patients in whom liver transplant exception points would be awarded (eg, patients with decompensated cirrhosis and LR-4 observation ≥ 2 cm in maximum diameter).…”
Section: Management Of Ilnsmentioning
confidence: 99%
“…Beyond the risk of prevalent HCC, ILNs also carry a high but variable risk of incident HCC during follow-up, with the strongest risk factor for HCC being the type of ILN (LR-3 vs. LR-4 observation). A systematic review demonstrated that 11.1%–24.5% of patients with LR-3 observations develop HCC over time, compared to 30.9%–71.0% of LR-4 observations 7 . Most patients with LR-4 observations who develop HCC do so in the first 6 months of follow-up, highlighting that most HCC are prevalent.…”
Section: Introductionmentioning
confidence: 99%